Vibrated and self-compacting fibre reinforced concrete: experimental investigation on the fibre orientation - Conforti, A. (2017)
In addition to the fibre type and content, the residual properties of fibre reinforced concrete are influenced by fibre orientation. Consequently, the performance fibre reinforced concrete can be affected by its fresh properties (workability, flowing capacity) and by casting and compaction processes adopted. This paper focuses on the study of the orientation of steel or macro-synthetic fibres in two materials characterized by very different fresh properties: vibrated and self-compacting concrete. Four rectangular slabs 1800 mm long, 925 mm wide and 100 mm high were produced changing concrete and fibre type. From each slab, eighteen small prisms (550 mm long) were firstly cut either orthogonal or parallel to casting direction and, secondly, notched and tested in bending according to EN 14651. Experimental results showed that the toughness properties of a thin slab significantly varies both in vibrated and self-compacting concrete, even if in case of self-compacting concrete this variation resulted higher. Steel fibres led to greater variability of results compared to polymer one, underlining a different fibre orientation. A discussion on the relative residual capacity measured on the prisms sawn from the slabs and the parameters obtained from standard specimens is performed.